Clinical Profile and Outcome among Infants of Diabetic Mothers Delivered At the Brooklyn Hospital Center - Uchendu, Uchendu O.; Leblanc, Patrick; Thomas, Jude M.; Maher, Ossama M.; Morales, Yesenia; Fineza, Belen (International Journal of Child Health and Nutrition, 2014)
Background: Diabetes mellitus (DM) is the commonest complication of pregnancy, negatively impacting mothers and fetuses. Few studies suggest amelioration of negative outcomes of DM-associated pregnancies in recent years, due in part to improved care. But increasing prevalence of overweight in developed countries is also affecting many women of childbearing age with concomitant poor glycemic control especially in pregnancy. Hyperglycemia, even at sub-diabetic levels, is associated with increased risk of macrosomia and Cesarean section. There is evidence demonstrating that outcomes of DM-associated pregnancies are similar with those characterized by hyperglycemia of sub-diabetic levels. Perhaps, improvement of care for DM-associated pregnancies on one hand, and the impact of obesity epidemic may have changed the relative frequencies of negative outcomes typically reported for infants of diabetic mothers (IDMs) compared with controls. Aims/Objective: We re-evaluated the relative frequencies of negative outcomes of pregnancies complicated by DM compared with non-diabetic pregnancies. Method/Design: A retrospective cohort analysis was conducted. Result: There were 50 diabetic and 83 non-diabetic mother-infant pairs. Mothers with DM-associated pregnancies had increased risk of delivery by C/Sxn, macrosomic babies, admission to NICU and prolonged hospitalization. Only IDMs had documented birth defects. Notable improvements over previous studies for IDMs include similar gestational ages at delivery and excellent APGAR scores in both groups. Conclusion: IDMs still have higher frequencies of negative outcomes compared with controls but some improvements are noteworthy and should provide impetus for efforts at reducing prevalence of obesity while improving care for DM-associated pregnancies.